Atrial natriuretic peptide (ANP) and oxytocin-expression in the adult rat and mouse cerebellum. Issue 1 (December 2015) - Lipari, Alessio; Farina, Elvira; Gerbino, Aldo; Lipari, Luana
Abstract Background Many studies are in the literature on the ANP and oxytocin-presence in the brain, but very few studies with controversial results are reported on the presence of these peptides in the cerebellum. This immunohistochemical study investigates on the ANP and oxytocin-presence in the cerebellum of the adult rat and mouse rodents. Results This study, firstly, evidences the ANP- immunopositivity in cerebellar cortex of both rat and mouse rodents. In rat the molecular layer presents some few immunopositive fibers, but no neuron resulted immunopositive; the granular and Purkinje cells are immunopositive. In mouse the cerebellar cortex ANP-immunopositivity is present in all layers. The oxytocin-presence in the rat the afferent fibers are immunopositive are in the granular layer; in mouse the OT-immunopositivity is in the molecular layer only. Conclusions This study, firstly, shows that ANP and OT are present in the cerebellar cortex both in rat and mouse rodents. In the mouse cerebellar cortex ANP-presence is more diffuse and OT- localization differences in the two species.